Production of Xylanase by a Bacillus sp. 2B5 Isolated from Paper Mills in Kahramanmaras, Turkey - KIRAN, OZLEM; UCAR, GULSUM (Asian Journal of Chemistry, 2010)
In this study, xylanase activity of Bacillus sp. strains, isolated from the samples of soil and waste taken from nearby paper-mills in Kahramanmaras. Enzyme synthesis occured at 20-55 °C. There was a slight variation in xylanase synthesis within the pH 4.0 to10.5. It has been determined that xylanase enzyme performs the optimum activity at pH 7.0 and 42 °C temperature.